Effects of trunk girdlin on fruit production, fruit size and tree vigor on 'Bartlett' pears in Río Negro and Neuquén Valley, Argentina - Raffo Benegas, Maria Dolores (2011)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010